基于Pro/E的非对称渐开线斜齿圆柱齿轮参数化设计及应力分析 - 李宁; 刘宁; 李威 (Jixie chuandong)
Helical gear with asymmetric involute is a new type of gear,and it hadn’t been studied in detail.According to gear generating method,curve sections on rack cutter are connected with curve section on helical gear.The equations of involute and fillet curve which are on helical gear driving side and driven side are derived.Based on curve equation of gear transverse section and combining with Pro/E software,a 3D model of helical gear with asymmetric involute is created.A new gear model could be regenerated by changing basic parameters because the model is parameterized.At two special engagement positions,the bending stress of helical gear with symmetric and asymmetric involute is analyzed and compared by FEA software.